Spatial updating in virtual reality: the sufficiency of visual information - Riecke, Bernhard E.; Cunningham, D. W.; Bülthoff, H. H. (Psychological Research, 2007)
Robust and effortless spatial orientation critically relies on "automatic and obligatory spatial updating", a largely automatized and reflex-like process that transforms our mental egocentric representation of the immediate surroundings during ego-motions. A rapid pointing paradigm was used to assess automati℅bligatory spatial updating after visually displayed upright rotations with or without concomitant physical rotations using a motion platform. Visual stimuli displaying a natural, subject-known scene proved sufficient for enabling automatic and obligatory spatial updating, irrespective of concurrent physical motions. This challenges the prevailing notion that visual cues alone are insufficient for enabling such spatial updating of rotations, and that vestibular/proprioceptive cues are both required and sufficient. Displaying optic flow devoid of landmarks during the motion and pointing phase was insufficient for enabling automatic spatial updating, but could not be entirely ignored either. Interestingly, additional physical motion cues hardly improved performance, and were insufficient for affording automatic spatial updating. The results are discussed in the context of the mental transformation hypothesis and the sensorimotor interference hypothesis, which associates difficulties in imagined perspective switches to interference between the sensorimotor and cognitive (to-be-imagined) perspective.
Keywords: Riecke; Riecke_2007; bernhard-riecke; iSpaceWeb; journalPaper; spatial updating; vection